Thermo-pneumatic micropump for drug delivery applications - Abdul Hamid, Norihan; Yeop Majlis, Burhanuddin; Yunas, Jumril; Ibrahim, Mazree (Asian Journal Of Medical Technology, 2022)
Micropumps constitute an essential part of precise delivery and directional volume control of fluid in a microfluidic system. In biomedical applications, micropump is widely used especially in drug delivery, biological fluid transmission, organic analysis, liquid measurement, and many more. In this paper, the concept and design structure hence fabrication of the Thermopneumatic micropump prototype are explained. The experimental measurement of the micropump employing planar diffuser nozzle in transmits fluid is also presented. Thermopneumatic micropump is comprised of three different components which are the microheater on the bottom, the flexible thin membrane that acts as an actuator, and the planar diffuser nozzle on the top to channel the fluidic. These three components were fabricated separately due to the different materials and techniques used in each component. Finally, the whole micropump system was integrated using an anodic bonding technique. Bulk micromachining technique was used to fabricated the chamber and thin-film membrane, surface micromachining technique for the microheater while replica molding technique was used for the planar diffuser nozzle. The whole diameter size for the micropump was 25 x 20 x 1.6 mm respectively. The microscope image recorded video and data was used during the experimental measurement, to observed and calculate the flow rate of meniscus motion flow in the outlet tube of the micropump. At the end of the experiment, the flow rate range of the micropump measure was approximately 770pL to 12.5nL, when the output of 2-12Vdc was applied to the microheater. This flow rate range is very suitable for drug delivery applications.